Ownership concentration and liquidity : the case of industrial sector in Malaysia - Tan, Seow Lin. (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This paper aims to present evidences that liquidity is significantly determined by ownership concentration besides than firm size, leverage and growth opportunities. The study focuses on the relations between ownership concentration and liquidity of Malaysian public listed firms in the industrial sector from year 2006 to 2010. The sector was selected due to its significance as the economy's indicator since Malaysia is developing and advancing into further stage of economy. The findings yielded that both insiders blockholders and institutional blockholders shown a ~ifferent results when measured by different liquidity measurements composed of dollar volume, turnover and bid-ask spread. This paper contribute to the existing literatures in the corporate governance field as there is limited empirical which study on Malaysia. Meanwhile, policy and law makers can use this study as a guideline to improve the firms' capital structure as well as the economic conditions which were both influenced by corporate liquidity.